Application of Halal Tourism Village Development Based on BUMDESA in East Java: Interpretive Structural Modeling (ISM) Approach - Nova Haryanto; Ridan Muhtadi; Moh. Fudholi (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2022)
This study aims to analyze the problems that occur in the development of halal tourism villages based on Village Owned Enterprises (BUMDesa) and see the priority problems and the most important solutions for developing halal tourism villages in East Java. The data was taken based on the results of questionnaires and in-depth interviews from nine experts consisting of three categories, namely, academics, practitioners and regulators. The method used is the Interpretive Structural Modeling (ISM) approach, and the data processing is done using software DDSS v.01. The results of this study indicate that based on the results of the study of literature studies and expert validation that the problems of developing a halal tourism village consist of regulatory issues, human resources, infrastructure, village conditions and government. Based on the results of the processed data, it shows that the most important priority problems in the development of halal tourism villages are village conditions, regulations, infrastructure, human resources and the government.Keywords: Halal Tourism Village, BUMDesa, Interpretive Structural Modeling